Montenegro Policy Note on Broadband : Achieving Universality of High-Speed Broadband - Review and Application Experience of the EU State Aid Framework - World Bank (Washington, DC, 2017)
Montenegro Policy Note on Broadband: Achieving Universality of High-Speed Broadband: Review and Application Experience of the EU State Aid Framework aims to provide advice to the Government of Montenegro on the possible mechanisms for state aid support for broadband infrastructure, while taking into account the State aid policy of the European Union (EU) and building on EU experience of similar projects. The objective is to support the development of the affordable access to broadband Internet in the un- and underserved geographical areas of Montenegro.